Method of projects on informatics lesson - as means of pupils’ informative competency - Staryh О. (Journal of Information Technologies in Education (ITE), 2007)
Information competence forms most effectively by pupils under joint execution of three conditions: problem-solving education, using of multimedia technologies and drafts method. Untraditional lessons that are conducted in Kherson Academical Lyceum help to arouse children’s longing to self-education, realization of their abilities.